Project-based learning as an alternative solution for learning computer basics during the Covid-19 pandemic - Wulandari, Yunita Oktavia; Khasanah, Fitria; Octavianti, Cynthia Tri (International Journal for Educational and Vocational Studies, 2022)
This study aims to obtain a meaningful alternative learning in computer basics courses during the covid-19 pandemic. The Covid-19 pandemic has gradually changed the educational paradigm, namely learning that was initially carried out synchronously into asynchronous Learning. It is at this time that all elements adapt to find effective solutions in carrying out meaningful Learning. In this study, Project-Based Learning will be designed in Computer Basics learning as a solution to make meaningful asynchronous Learning. Project-Based Learning was chosen because it has characteristics that are process-centred, problem-focused, combining the concepts of several components, both knowledge, disciplines, and field experience. The study subjects were college students of class Computer Basics, with a total of 11 students. There are two projects in this study with three steps which are planning the project, implementation the project, and evaluating the project. The result of this study is that meaningful learning alternatives are obtained for prospective mathematics teacher students in the Computer Basics course so that in the future, they can hone their creativity.